The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/app13137769
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Collaborative Control Method for Multi-Axle Distributed Vehicle Assisted Driving

Abstract: For human–machine collaborative driving conditions, a hierarchical chassis multi-objective cooperative control method is proposed in this paper. Firstly, based on the phase plane theory, vehicle dynamics analysis is carried out to complete the definition of vehicle stability region. Secondly, based on the linear time-varying (LTV) system model, a cooperative control strategy combining fuzzy control with model predictive control (MPC) is proposed in the upper layer. In this strategy, the assisted driving weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…For multi-axle distributed vehicles, stability weight adjustment coefficients were introduced in the torque distribution strategy to achieve the multi-objective optimization of the tire load rate and energy efficiency. The simulation analysis results showed that the torque distribution can be reduced by approximately 8% in energy consumption compared to the inter-axle torque allocation strategy [22]. To reduce energy consumption during the steering condition for multi-axle electric vehicles, the deep deterministic policy gradient (DDPG) algorithm was proposed, resulting in a decrease of approximately 5% in the maximum SOC degradation rate of the vehicle [23].…”
mentioning
confidence: 99%
“…For multi-axle distributed vehicles, stability weight adjustment coefficients were introduced in the torque distribution strategy to achieve the multi-objective optimization of the tire load rate and energy efficiency. The simulation analysis results showed that the torque distribution can be reduced by approximately 8% in energy consumption compared to the inter-axle torque allocation strategy [22]. To reduce energy consumption during the steering condition for multi-axle electric vehicles, the deep deterministic policy gradient (DDPG) algorithm was proposed, resulting in a decrease of approximately 5% in the maximum SOC degradation rate of the vehicle [23].…”
mentioning
confidence: 99%